Monty Python's The meaning of life [videorecording (Blu-Ray)] - Jones, Terry, 1942-2020; Jones, Terry, 1942-2020; Chapman, Graham, 1941-1989; Chapman, Graham, 1941-1989; Cleese, John; Cleese, John; Gilliam, Terry; Gilliam, Terry; Idle, Eric; Idle, Eric; Palin, Michael; Palin, Michael (Universal Studios Home Entertainment, 2013)
Monty Python is back to explain The Meaning of Life. Those naughty Brits offer the usual tasteful sketches involving favorite body parts and bodily functions, the wonders of war, the miracle of birth and a special preview of what's waiting for us in Heaven.